Comparative Analysis of Utility and Efficacy of Ozone Therapy versus Laser Therapy in Periarthritis Shoulder - Sunil Kumar; Harish Kumar; Prashant Pratap Singh; Dinesh Kumar; Vyutpanna Mishra; Ishan Ahmad (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Adhesive capsulitis of shoulder due to uncertain etiology of glenohumeral joint characterized by spontaneous onset of pain and reduction in the arc of active and passive movements at glenohumeral joint and essentially normal radiograph. It is considered a self-limiting condition with a natural history of 1–3 years while some have refractory course. Most of adhesive capsulitis patients are successfully treated with nonsurgical treatment such as non-steroidal anti-inflammatory drugs (NSAIDS), oral/intra-articular corticosteroids, and hydrodialtation, among nonsurgical modalities, ozone and laser are newer, safe, and show promising results in adhesive capsulitis management. A current study was done to compare between ozone therapy and laser therapy in terms of efficacy and utility in periarthritis shoulder. Materials and Methods: All patients who presented with shoulder pain and stiffness at the orthopedics outpatient department of tertiary care center of rural North India, on the basis of clinical history and examination, those who were diagnosed with adhesive capsulitis and fulfilling the inclusion criteria and exclusion criteria were included in the study, after obtaining proper informed and written consent, cases were randomized into two groups for laser and ozone therapy. Results: A total of 55 patients were included in the study, among them, 42 patients (20 patients in the laser and 22 in the ozone group) were followed up to a final follow-up of 6 months and 13 patients lost their follow-up. Disabilities of the arm, shoulder, and hand questionnaire (DASH) score ozone group showed a gradual decline from the preinjection score of 55.68–17.78 at 6 months. In the laser group, there is also a decline in DASH scores from the pretreatment score of 57.56–23.34 at 6 months. Difference in DASH score was insignificant up to 4 weeks across both groups. On follow-up after 4 weeks up to 6 months showed a significant difference in DASH score across both groups. Decline in the ozone group was more as compared to the laser group (P < 0.026). Conclusion: Both ozone and laser are safe and effective modalities of treatment of adhesive capsulitis but ozone is more effective in long term.